ANALISIS SEMIOTIKA ANTI KORUPSI DALAM MURAL KARYA KOMUNITAS PEVIART DI KOTA PEKANBARU - Aiza Nofianti; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Mural usually used as room decoration and now more used as a conveyor of aspiration. Like the murals with anti-corruption theme created by the Peviart Community. This mural contains criticism and message to eliminate the culture of corruption in Bumi Lancang Kuning. The problem of corruption is a complex problem that often happens and now keep increasing. Therefore, this study aims to determine the meaning of anti-corruption contained in the mural by Peviart community in Pekanbaru City.This research uses qualitative research methods and supported by the theory of semiotic analysis of Charles Sanders Pierce. Subjects in this study were determined based on purposive sampling technique consisting of three mural images entitled #SAVEUANGMAMAK, Mewah Karena Korupsi, and Asingkan Koruptor dari Muka Bumi. The data collection techniques include observation, documentation, and literature study. The data analysis technique used is Charles Sanders Peirce’s analysis of semiology with triadic models, where the representament, object and interpretant have mutually fulfilling relationship strength and advantages with data validity checking done using triangulation techniques.The results of this research show that the Peviart Community mural in terms of shape, color, and illustration has the meaning of corruption and anti corruption behavior itself. In the mural entitled #SAVEUANGMAMAK and Mewah Karena Korupsi shows more of the meaning of corruption, this act of corruption is shown so that people who see it do not commit the act of corruption. While on the mural entitled Asingkan Koruptor dari Muka Bumi show more anti-corruption meaning, the meaning shown is the corruptor that must be eradicated and the role of KPK in combating corruption. Overall, the anti-corruption semiotics analysis in the three mural images of the peviart community is a corrupt person who has a fat body, corruption to enrich himself, corruption done by officials, yellow as a symbol of wealth, and the KPK as a symbol of anti-corruption. Keywords: Analysis, Semiotics, Peirce’s Semiotic, Mural, Anti-corruption.